Carbonate carbon-loaded cement, preparation method thereof and carbonate carbon-loaded cement product
A carbonated cement composition with mixed calcium magnesium phases, processed through controlled carbonization, addresses the high-cost and low-strength issues of existing cements, achieving enhanced strength and CO2 sequestration for low-carbon construction.
Patent Information
- Application Number
- CN202311276912.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
Current carbonated cement production methods consume vast resources and energy, leading to significant CO2 emissions, and existing carbonated cements with calcium carbonate as the primary material have low strength and high production costs, limiting their application in achieving 'zero' or 'negative' carbon emissions.
A carbonated cement composition comprising a mixture of unstable and hydrated calcium magnesium phases, including various crystal forms of calcium magnesium, which are converted through a controlled carbonization process using water-based materials and active agents to enhance strength and reduce production costs.
The resulting carbonated cement exhibits improved strength, reduced water demand, and enhanced CO2 sequestration capabilities, making it suitable for low-carbon construction applications and facilitating 'negative' carbon emissions throughout its lifecycle.
Smart Images

Figure CN119707384A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and in particular relates to a carbonate negative carbon cement and a preparation method thereof, and a carbonate negative carbon cement product. Background Art
[0002] As the global population increases, people's demand for residential buildings has led to the rapid development of the construction industry. However, the current cement production process of "two grindings and one burning" consumes a lot of resources and energy, and emits a huge amount of carbon dioxide, which has caused a series of problems such as global warming and sea level rise. In order to achieve the goal of carbon neutrality, carbon dioxide storage and utilization technology is expected to achieve "zero carbon emissions" in the cement industry, or even "negative carbon emissions" throughout the life cycle. Therefore, the development and utilization of carbonate negative carbon cement is of great significance.
[0003] At present, the main raw material of carbonate negative carbon cement is mostly vaterite calcium carbonate. The strength of the subsequently prepared calcium carbonate gel or cement products is relatively low, and the preparation method of vaterite calcium carbonate mostly adopts a mixture of soluble calcium salt solution and carbonate, which is costly and the preparation method is relatively simple. It is difficult to use other crystalline carbonate precursors to prepare carbonate negative carbon cement. Summary of the invention
[0004] The purpose of this application is to provide a carbonate negative carbon cement and a preparation method thereof, and a carbonate negative carbon cement product, aiming to solve the problem of how to provide a carbonate negative carbon cement with low cost and good performance.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a carbonate negative carbon cement, comprising the following components in parts by weight:
[0007]
[0008]
[0009] The calcium magnesium carbonate comprises a metastable calcium magnesium carbonate phase and a hydrous calcium magnesium carbonate phase, and a weight ratio of the metastable calcium magnesium carbonate phase to the hydrous calcium magnesium carbonate phase is 1:(0-1).
[0010] In some embodiments, the metastable calcium magnesium carbonate phase is an anhydrous crystalline phase, including at least one of vaterite calcium magnesium carbonate, aragonite calcium magnesium carbonate and calcite calcium magnesium carbonate; and / or,
[0011] The hydrated calcium magnesium carbonate phase includes at least one of amorphous calcium magnesium carbonate, hexahydrate calcium magnesium carbonate, monohydrate calcium magnesium carbonate and hemihydrate calcium magnesium carbonate.
[0012] In some embodiments, the mass percentage of magnesium in the metastable calcium magnesium carbonate phase is 0.1-18%, and the average particle size is 0.1 μm-3 mm.
[0013] In some embodiments, the mass percentage of crystal water in the hydrous calcium carbonate magnesium phase is 5-60%, the mass percentage of magnesium is 0.1-20%, and the average particle size is 0.1 μm-10 μm.
[0014] In some embodiments, the calcium magnesium carbonate is obtained by mixing cement-based materials with an active enhancer and then subjecting the mixture to carbonization treatment.
[0015] In some embodiments, the cement-based material includes at least one of concrete sand powder, steel slag, cement powder, slag, carbide slag, phosphogypsum, red mud, and magnesium slag; and / or,
[0016] The activity enhancer includes at least one of soluble magnesium salt, magnesium hydroxide, magnesium oxide, ethylenediaminetetraacetic acid, chitosan, tannic acid and amino acid.
[0017] In some embodiments, the total amount of the activity enhancer added is 1-10% of the mixture to be carbonized; and / or
[0018] The carbonization treatment includes: introducing gas with a carbon dioxide concentration of not less than 5% for carbonization, and according to the solid mass of the cement-based material, the gas introduction rate is 0.01L / min / g-2L / min / g, and the introduction time is 1min-6h.
[0019] In some embodiments, the clinker comprises at least one of Portland cement, sulphoaluminate cement, sulfate cement and magnesium oxide cement; and / or,
[0020] The mineral admixture includes at least one of fly ash, slag, steel slag and concrete powder; and / or,
[0021] The coagulation regulator includes at least one of soluble magnesium salt, phosphate, gypsum, ethylenediaminetetraacetic acid, chitosan, tannic acid, and amino acid; and / or,
[0022] The water reducer includes at least one of lignin sulfonate water reducer, polycyclic aromatic salt water reducer, water-soluble resin sulfonate water reducer, naphthalene water reducer, aliphatic water reducer, amino water reducer and polycarboxylic acid water reducer.
[0023] In a second aspect, the present application provides a method for preparing carbonate negative carbon cement, comprising:
[0024] The raw materials of each component in the carbonate negative carbon cement described in this application are provided:
[0025] The calcium magnesium carbonate, the clinker, the mineral admixture, the setting regulator and the water reducer are mixed to obtain the carbonate negative carbon cement.
[0026] In a third aspect, the present application provides a carbonate negative carbon cement product, which is obtained by mixing the carbonate negative carbon cement of the present application and / or the carbonate negative carbon cement prepared by the preparation method of the present application with water, and then undergoing molding and curing treatment.
[0027] The carbonate negative carbon cement provided in the first aspect of the present application includes a certain weight portion of calcium magnesium carbonate, clinker (can be added or not), mineral admixtures (can be added or not), a setting regulator and a water reducer; wherein, the calcium magnesium carbonate includes a metastable calcium magnesium carbonate phase and a hydrated calcium magnesium carbonate phase, and calcium magnesium carbonate of various crystal forms are used as phase change precursors in carbonate negative carbon cement to transform the crystal form into a source of bonding force, which is more conducive to improving the carbon dioxide sequestration capacity and contributing to the smooth realization of low-carbon goals. Moreover, the carbonate negative carbon cement of the present application has low hydration heat, high strength, and is easy to preserve, and has great application in the production and construction of concrete and concrete products.
[0028] The preparation method of carbonate negative carbon cement provided in the second aspect of the present application is obtained by mixing the various component raw materials in the carbonate negative carbon cement of the present application. The carbonate negative carbon cement obtained in this way is beneficial to improving the storage capacity of carbon dioxide. Moreover, the preparation method is simple in process, and the obtained cement has high activity and is easy to preserve, which is beneficial to storage and transportation during the production process.
[0029] The carbonate negative carbon cement product provided in the third aspect of the present application is formed by the carbonate negative carbon cement of the present application, and therefore has good carbon dioxide storage capacity, high mechanical properties, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 The optional types of calcium magnesium carbonate in the carbonate negative carbon cement provided in the embodiments of the present application are: X-ray diffraction patterns of hydrated calcium magnesium carbonate phase, vaterite calcium magnesium carbonate, aragonite calcium magnesium carbonate, and calcite calcium magnesium carbonate;
[0032] Figure 2The optional types of calcium magnesium carbonate in carbonate negative carbon cement provided in the embodiments of the present application are scanning electron microscope images of hydrated calcium magnesium carbonate phase, vaterite calcium magnesium carbonate, aragonite calcium magnesium carbonate, and calcite calcium magnesium carbonate;
[0033] Figure 3 is a hydration heat flow curve diagram of carbonate negative carbon cement provided in Example 1 of the present application;
[0034] Figure 4 This is a scanning electron microscope image of the carbonate negative carbon cement product provided in Examples 1-4 of the present application 28 days after being made. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0036] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0037] In the present application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.
[0038] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0039] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0040] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0041] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0042] In a first aspect, an embodiment of the present application provides a carbonate negative carbon cement, comprising the following components in parts by weight:
[0043]
[0044]
[0045] The calcium magnesium carbonate includes a metastable calcium magnesium carbonate phase and a hydrous calcium magnesium carbonate phase, and a weight ratio of the metastable calcium magnesium carbonate phase to the hydrous calcium magnesium carbonate phase is 1:(0-1).
[0046] The embodiment of the present application provides a carbonate negative carbon cement with low cost and a wide range of crystal transformation precursors, which forms a high mechanical strength through the transformation of multiple crystal forms. Specifically, the use of calcium magnesium carbonate of multiple crystal forms as phase change precursors in carbonate negative carbon cement to transform the crystal form into a source of bonding force is more conducive to improving the storage capacity of carbon dioxide and contributing to the smooth realization of low-carbon goals. In addition, the carbonate negative carbon cement of the embodiment of the present application has low hydration heat, high strength, and is easy to store, and has a good application in the production and construction of concrete and concrete products.
[0047] In some embodiments, the metastable calcium magnesium carbonate phase is an anhydrous crystalline phase, including at least one of vaterite calcium magnesium carbonate, aragonite calcium magnesium carbonate and calcite calcium magnesium carbonate; the hydrated calcium magnesium carbonate phase includes at least one of amorphous calcium magnesium carbonate, hexahydrate calcium magnesium carbonate, monohydrate calcium magnesium carbonate and hemihydrate calcium magnesium carbonate. All of the above calcium magnesium carbonates can be prepared by a controlled carbonization method of cement-based materials. Specifically, the purity of calcium magnesium carbonate is greater than 75%.
[0048] The so-called negative carbon technology refers to strengthening the geological utilization of carbon dioxide, efficiently converting carbon dioxide into fuel chemicals, or directly capturing carbon dioxide from the air, biochar soil improvement and other carbon negative emission technologies. The carbonate negative carbon cement in the embodiment of the present application refers to cement production and use that can bring negative carbon dioxide emissions, that is, absorb and store carbon dioxide from the atmosphere, thereby having a positive effect on the environment.
[0049] The main component of the carbonate negative carbon cement of the embodiment of the present application is calcium magnesium carbonate. In the saturated pore water solution, calcium magnesium carbonate can participate in the process of "dissolution-recrystallization" and phase-transform into calcium magnesium carbonate in a more thermodynamically stable state. For example, some organisms (shells, cuticles, shells of soft animals, etc.) can very accurately regulate the process of calcium magnesium carbonate phase transition, and directionally regulate the phase transition of hydrated calcium magnesium carbonate into calcite calcium magnesium carbonate or aragonite calcium magnesium carbonate, thereby forming extremely high mechanical properties. At the same time, some highly active calcite or aragonite calcium magnesium carbonate (high magnesium) can also be transformed into stable calcite or aragonite calcium magnesium carbonate (low magnesium) through the process of "dissolution-recrystallization". In the process of direct or indirect carbonization of cement-based materials, by controlling the carbonization time, carbonization temperature, active enhancer, etc., various crystalline calcium magnesium carbonates can be prepared, the main components of which are hydrated calcium magnesium carbonate phase (amorphous calcium magnesium carbonate, hexahydrate calcium magnesium carbonate, monohydrate calcium magnesium carbonate, hemihydrate calcium magnesium carbonate) or / and metastable calcium magnesium carbonate phase (vaterite calcium magnesium carbonate, vaterite calcium magnesium carbonate, calcite calcium magnesium carbonate). By simulating the process of shell biomineralization, the above-mentioned crystalline calcium magnesium carbonate can be used as the main reaction precursor of the "dissolution-recrystallization" process, and the phase changes to more stable low-magnesium calcite or low-magnesium aragonite crystals. At the same time, since the phase change rate of some calcium magnesium carbonates is too fast, a setting regulator is added to adjust the setting time and control its nucleation growth rate to meet the construction requirements.
[0050] Specifically, highly active calcium magnesium carbonate refers to calcium magnesium carbonate that is prone to crystal transformation; highly active calcium magnesium carbonate can spontaneously undergo a "dissolution-recrystallization" process under humid conditions, transforming from one crystal form to another. High magnesium in calcium magnesium carbonate generally refers to a magnesium content that can account for more than or equal to 4% of the total weight of calcium magnesium carbonate, such as a magnesium content of 4-20%, and low magnesium in calcium magnesium carbonate generally refers to a magnesium content that accounts for less than 4% of the total weight of calcium magnesium carbonate, such as a magnesium content of 0.1-3.8%. For highly active calcium magnesium carbonate, calcium magnesium carbonate with a high magnesium content is generally included.
[0051] In some embodiments, the metastable calcium magnesium carbonate phase includes: 50-100 parts of vaterite calcium magnesium carbonate. Alternatively, the metastable calcium magnesium carbonate phase includes: 10-90 parts of vaterite calcium magnesium carbonate and 10-50 parts of vaterite calcium magnesium carbonate. Alternatively, the metastable calcium magnesium carbonate phase includes: 20-70 parts of vaterite calcium magnesium carbonate, 10-50 parts of vaterite calcium magnesium carbonate and 20-50 parts of calcite calcium magnesium carbonate. The metastable calcium magnesium carbonate phase is an anhydrous crystalline phase with a magnesium content of 0.1-18% and an average particle size of 0.1 μm-3mm.
[0052] In some embodiments, the hydrated calcium magnesium carbonate phase includes one or more of amorphous calcium magnesium carbonate, hexahydrate calcium magnesium carbonate, monohydrate calcium magnesium carbonate, and hemihydrate calcium magnesium carbonate, and the proportions are arbitrary when multiple types are included; the hydrated calcium magnesium carbonate phase has a water content (crystallization water) of 5-60%, a magnesium content of 0.1-20%, and an average particle size of 0.1-10 μm.
[0053] In some embodiments, the weight ratio of the metastable calcium magnesium carbonate phase to the hydrated calcium magnesium carbonate phase is 1: (0-1), that is, the hydrated calcium magnesium carbonate phase can be added or not as needed. When the hydrated calcium magnesium carbonate phase is added, the weight ratio of the metastable calcium magnesium carbonate phase to the hydrated calcium magnesium carbonate phase can be 1: 0.1, 1: 0.2, 1: 0.4, 1: 0.5, 1: 0.6, 1: 0.8, 1: 1, etc.
[0054] In some embodiments, calcium magnesium carbonate is obtained by mixing cement-based materials with an active enhancer and then carbonizing them. Calcium magnesium carbonate of various crystal forms is prepared by controllable carbonization of cement-based materials and used as a phase change precursor in carbonate negative carbon cement.
[0055] The main component of carbonate negative carbon cement is calcium magnesium carbonate prepared by controlled carbonization of cement-based materials, including hydrated calcium magnesium carbonate phase and / or metastable calcium magnesium carbonate phase, which breaks through the limitation of aragonite and calcite as crystal transformation precursors. Such carbonate negative carbon cement has high activity and is easy to preserve. It can still retain its activity for a long time under dry conditions, which is conducive to storage and transportation during the production process.
[0056] In some embodiments, the cement-based material includes at least one of industrial and construction solid wastes such as concrete sand powder, steel slag, cement powder, slag, carbide slag, phosphogypsum, red mud, and magnesium slag; the powder particle size of the cement-based material is ≤0.15 mm, and the total calcium and magnesium content of the cement-based material is not less than 30%. By utilizing cement-based materials with high added value, a new direction for the utilization of cement-based materials is provided. The activity enhancer includes at least one of soluble magnesium salts, magnesium hydroxide, magnesium oxide, ethylenediaminetetraacetic acid, chitosan, tannic acid, and amino acids. By mass, the total amount of the activity enhancer added is 1-10% of the total weight of the mixture to be carbonized. If the magnesium content of the cement-based material is less than 5%, there is at least one magnesium-containing activity enhancer in the activity enhancer; the activity enhancer selected for preparing the hydrated calcium carbonate magnesium phase should also include chitosan, tannic acid, and amino acids. The activity enhancer selected for preparing the highly active vaterite-type calcium carbonate magnesium should also include ammonia water or an alkaline mixture containing ammonium salts.
[0057] The raw materials for the preparation of calcium magnesium carbonate mainly come from construction solid waste of cement-based materials. The cost is low, and it can turn waste into treasure, which is conducive to the realization of industrial large-scale preparation. As the main component of carbonate negative carbon cement, calcium magnesium carbonate can be prepared by carbonizing cement-based materials, including direct carbonization and indirect carbonization, both of which can prepare hydrated calcium magnesium carbonate phase and metastable calcium magnesium carbonate phase. The direct carbonization method is to mix cement-based materials with active enhancers for carbonization, and filter, wash and dry the carbonized products to obtain calcium magnesium carbonate; the indirect carbonization method is to prepare the leachate of cement-based materials, mix the leachate with active enhancers for carbonization, and filter, wash and dry the carbonized products to obtain calcium magnesium carbonate.
[0058] In some implementation cases, the direct carbonization method includes the following steps: mixing cement-based materials with solvents, adding an active enhancer, and directly introducing a gas containing carbon dioxide into the mixture after the mixture is evenly mixed for carbonization, and washing, filtering and drying the carbonized product to obtain calcium magnesium carbonate. The mass ratio of cement-based materials to solvents is 1: (1-20), and the total amount of active enhancers added is 1-10% of the mixture to be carbonized (the mixture to be carbonized in the direct carbonization method is cement-based materials).
[0059] In some implementation cases, the indirect carbonization method includes the following steps: mixing cement-based materials with solvents for leaching, filtering to obtain a leachate, mixing the leachate with an activity enhancer, introducing a carbon dioxide-containing gas into the mixture for carbonization, and washing, filtering and drying the carbonized product to obtain calcium magnesium carbonate. The leachate is selected from one or more of hydrochloric acid, sulfuric acid and acidic ammonium salts; wherein the mass ratio of cement-based materials to mixed solvents is 1:(1-20), and the leachate accounts for 0-10% of the total weight of the mixed solution; and the total amount of the activity enhancer added is 1-10% of the mixture to be carbonized (the mixture to be carbonized in the indirect carbonization method is a cement-based material leachate).
[0060] The above-mentioned activity enhancer may include at least one of soluble magnesium salt, magnesium hydroxide, magnesium oxide, ethylenediaminetetraacetic acid, chitosan, tannic acid, and amino acid; if the magnesium content of the cement-based material is less than 5%, at least one magnesium-containing activity enhancer is present in the activity enhancer. Optionally, the solvent may be an aqueous solvent, and the aqueous solvent is selected from one or more of incoming water, seawater, deionized water, and reclaimed water. Optionally, the solvent is a mixed solution containing a leaching agent and an aqueous solvent; wherein the leaching agent is selected from one or more of hydrochloric acid, sulfuric acid, and acidic ammonium salts; the leaching agent accounts for 0-10% of the total weight of the mixed solution.
[0061] In some embodiments, the filtration may be performed by conventional solid-liquid separation methods, such as one or more of centrifugation, sedimentation and pressure filtration. After filtration, the remaining liquid is recovered and reused to prepare the suspension slurry.
[0062] In some embodiments, the carbonization treatment includes: introducing a gas with a carbon dioxide concentration of not less than 5% for carbonization, and the gas introduction rate is 0.01L / min / g-2L / min / g, and the introduction time is 1min-6h, calculated based on the solid mass of the cement-based material.
[0063] Specifically, during carbonization, a carbon dioxide mixed gas with a concentration of not less than 5% is introduced, including tail gas from the cement industry, chemical industry, electricity, and waste incineration; by carbonizing carbon dioxide in the tail gas of the mineralization industry, the carbon emissions of building materials are reduced, which has important environmental benefits. Alternatively, carbon dioxide gas can be introduced directly. According to the mass of cement-based materials, the fixed carbon dioxide can reach 0.01-0.6g CO 2 / g cement-based material; specifically, it can be carried out under the conditions of 0-60°C and a stirring speed of 100-1000 rpm.
[0064] In some embodiments, the carbon dioxide ventilation time when preparing the hydrous calcium magnesium carbonate phase is 1-10 min, and the temperature is 0-20°C; the carbon dioxide ventilation time when preparing the high-activity vaterite calcium magnesium carbonate is 10-30 min, and the temperature is 0-40°C; the carbon dioxide ventilation time when preparing the high-activity aragonite calcium magnesium carbonate is 30-60 min, and the temperature is 40-60°C; the carbon dioxide ventilation time when preparing the high-activity calcite calcium magnesium carbonate is 2-6h, and the temperature is 20-40°C.
[0065] For example, the calcium carbonate magnesium prepared by the present application embodiment comprises hydrated calcium carbonate magnesium phase, high activity vaterite type calcium carbonate magnesium, high activity aragonite type calcium carbonate magnesium, and high activity calcite type calcium carbonate.Specific preparation process is as follows.The hydrated calcium carbonate magnesium, high activity vaterite type calcium carbonate magnesium, high activity aragonite type calcium carbonate magnesium and high activity calcite type calcium carbonate magnesium prepared are used in hereinafter embodiment 1-4.
[0066] In one embodiment, a high-activity vaterite type calcium magnesium carbonate preparation step comprises: 100g recycled concrete fine powder is dissolved in 1L ammonia chloride solution (concentration 1mol / L), stirred for 2h at a speed of 200 rev / min and 25 degrees Celsius, and separation and filtration obtains a leaching solution; 0.5mol of magnesium chloride and 1mol of ammonia water are added to the leaching solution, carbon dioxide gas is passed after uniform mixing, and the rate is 0.5L / min, and the time is 30min, and under the same conditions, it is stirred. After finishing passing into, vacuum filtration is carried out, and the isolated solid is cleaned with anhydrous ethanol 2 times, and finally dried for 24 hours at 20 degrees Celsius in a vacuum drying oven to obtain a high-activity vaterite type calcium magnesium carbonate. X-ray diffractometer (XRD) is utilized to carry out physical phase analysis, such as Figure 1 The product was found to be mainly high-activity vaterite-type calcium magnesium carbonate. The morphology was analyzed using a scanning electron microscope (SEM). Figure 2 It was found that the products were mostly spherical vaterite particles of 1-10 um, and the magnesium content in the crystalline phase was 11.4% in X-ray fluorescence spectrometer (XRF) analysis.
[0067] In one embodiment, a method for preparing a highly active aragonite calcium magnesium carbonate is as follows: 100 g of slag is dissolved in 1 L of ammonium sulfate solution (concentration 1 mol / L), stirred at 200 rpm and 25 degrees Celsius for 2 h, and separated and filtered to obtain a leaching solution; 1 mol of magnesium oxide is added to the leaching solution, and after uniform mixing, carbon dioxide gas is introduced at a rate of 0.5 L / min, and stirred at 200 rpm and 60 degrees Celsius for 1 h; after the introduction is completed, vacuum filtration is performed, and the separated solid is washed twice with anhydrous ethanol, and finally dried in a vacuum drying oven at 20 degrees Celsius for 24 hours to obtain highly active aragonite calcium magnesium carbonate. Using an X-ray diffractometer ( Figure 1 ) and scanning electron microscopy ( Figure 2 ) The obtained products were subjected to phase analysis and morphology analysis respectively, and most of the products were high-activity aragonite calcium magnesium carbonate, and the magnesium element accounted for 15.1% in XRF analysis.
[0068] In one embodiment, a method for preparing high-activity calcite-type calcium magnesium carbonate is as follows: 100g of carbide slag is dissolved in 1L of hydrochloric acid solution (concentration 1mol / L), stirred at a speed of 200 rpm and 25 degrees Celsius for 2h to obtain a mixture A, 1mol of magnesium hydroxide is added, and carbon dioxide gas is introduced by a direct carbonization method at a rate of 0.5L / min for 4h, and stirred under the same conditions; after the introduction is completed, vacuum filtration is performed, and the separated solid is washed twice with anhydrous ethanol, and finally dried in a vacuum drying oven at 20 degrees Celsius for 24 hours to obtain a high-activity calcite-type calcium magnesium carbonate. XRD of the carbonized product ( Figure 1 ) and SEM( Figure 2 ) showed that the product was almost highly active calcite-type calcium magnesium carbonate, with a magnesium content of 17.5% in XRF analysis.
[0069] In one embodiment, a method for preparing a hydrated calcium carbonate magnesium phase is as follows: 100g of red mud is dissolved in 1L of ammonium nitrate solution (concentration 1mol / L), stirred at 200 rpm and 25 degrees Celsius for 2h, and separated and filtered to obtain a leaching solution; 0.5mol of magnesium nitrate and 0.5mol of amino acid are added to the leaching solution, and then carbon dioxide gas is introduced at a rate of 0.5L / min for 5min, at a temperature of 0 degrees Celsius, and stirred at a speed of 200 rpm; after the introduction is completed, vacuum filtration is performed, and the separated solid is washed twice with anhydrous ethanol, and finally dried in a freeze dryer at -50 degrees Celsius for 24 hours to obtain a hydrated calcium carbonate magnesium phase. Using an X-ray diffractometer ( Figure 1 ) and scanning electron microscopy ( Figure 2 ) The obtained product was subjected to phase analysis and morphology analysis respectively, and the product was amorphous hydrated calcium magnesium carbonate. The magnesium content was 17.3% by XRF analysis.
[0070] In some embodiments, the clinker includes at least one of ordinary Portland cement, sulphoaluminate cement, sulfate cement, and magnesium oxide cement. The clinker weight portion is 0-20 parts, and it can be added or not added as needed.
[0071] In some embodiments, the mineral admixture includes at least one of fly ash, slag, steel slag, concrete powder and other industrial or construction solid wastes. The mineral admixture is 0-50 parts by weight and can be added or not added as needed.
[0072] In some embodiments, the coagulation regulator includes at least one of inorganic or organic crystal regulators such as soluble magnesium salts, phosphates, gypsum, ethylenediaminetetraacetic acid, chitosan, tannic acid, amino acids, etc. The coagulation regulator is present in an amount of 0.1-5 parts by weight and is used to adjust the coagulation time.
[0073] In some embodiments, the water reducer includes at least one of lignin sulfonate water reducer, polycyclic aromatic salt water reducer, water-soluble resin sulfonate water reducer, naphthalene water reducer, aliphatic water reducer, amino water reducer, and polycarboxylic acid water reducer. The weight portion of the water reducer is 0.5-5 parts.
[0074] In a second aspect, the present application provides a method for preparing carbonate negative carbon cement, comprising:
[0075] S01: Provide the raw materials of each component in the carbonate negative carbon cement of this application:
[0076] S02: Calcium magnesium carbonate, clinker, mineral admixtures, setting regulators and water reducers are mixed to obtain carbonate negative carbon cement.
[0077] The preparation method of the carbonate negative carbon cement in the embodiment of the present application is obtained by mixing the various component raw materials in the carbonate negative carbon cement in the embodiment of the present application. The carbonate negative carbon cement obtained in this way is beneficial to improving the storage capacity of carbon dioxide. Moreover, the preparation method is simple in process, and the obtained cement has high activity and is easy to preserve, which is beneficial to storage and transportation during the production process.
[0078] In a third aspect, an embodiment of the present application provides a carbonate negative carbon cement product, which is obtained by mixing the carbonate negative carbon cement of the embodiment of the present application and / or the carbonate negative carbon cement prepared by the preparation method of the embodiment of the present application with water, and then undergoing molding and curing treatment.
[0079] The carbonate negative carbon cement product of the embodiment of the present application is formed by the carbonate negative carbon cement of the present application, and therefore has good carbon dioxide storage capacity, high mechanical properties, and has broad application prospects.
[0080] In one embodiment, the curing includes one of air curing, carbonization curing or steam curing; the curing temperature is 20-100 degrees Celsius, and the relative humidity is 20-95%; if it is carbonization curing, the carbon dioxide concentration is 20-95%. The curing time can be 1-28 days. The final water-cement ratio of the basic construction fluidity is 0.15-1; the setting time is 4-24 hours; the hydration heat within 72 hours is 20-80 J / g cement solid; the 28-day flexural and compressive strengths are 4-11 MPa and 20-80 MPa respectively.
[0081] In summary, this application uses the crystal transformation of calcium magnesium carbonate as the source of bonding force. The crystal transformation precursors, pathways and products are diverse, the hydration heat is low, the strength is high, and the setting time, curing temperature and environment are similar to those of ordinary Portland cement, which is beneficial to the production and construction of concrete and concrete products. At the same time, it can be mixed with a variety of mineral admixtures with good adaptability. The ability of carbonate negative carbon cement to sequester carbon dioxide is not less than 60%, and the prepared calcium carbonate negative carbon cement has the characteristics of low carbon, and almost achieves "zero emissions" and "negative emissions" of carbon dioxide throughout the life cycle.
[0082] The following is described in conjunction with specific embodiments. It should be noted that the corresponding preparation processes of the hydrous calcium magnesium carbonate, high-activity vaterite-type calcium magnesium carbonate, high-activity aragonite-type calcium magnesium carbonate and high-activity calcite-type calcium magnesium carbonate provided in the following embodiments are referred to above.
[0083] Example 1
[0084] A carbonate negative carbon cement, comprising the following solid raw materials in parts by weight: 100 parts of high-activity vaterite-type calcium magnesium carbonate ( Figure 2 Highly active vaterite type calcium magnesium carbonate product), 20 parts of ordinary Portland cement, 10 parts of fly ash, 5 parts of gypsum, and 5 parts of polycarboxylate water reducer.
[0085] The raw materials of carbonate negative carbon cement were mixed in a stirring pot, stirred evenly for 5 minutes, and then water was added to the stirring pot at a water-to-solid ratio of 0.2. After stirring evenly for 3 minutes, a carbonate negative carbon cement slurry was obtained. The heat of hydration heat of the prepared cement slurry for 72 hours was as follows: Figure 3 As shown, the heat of hydration in 72 hours is 42 J / g solid, which is 20-30% of ordinary Portland cement. The cement paste was poured into a standard compression and flexural test block mold and placed in air curing at 20 degrees Celsius for 28 days. The curing humidity was 95%. The flexural and compressive strengths at 28 days were 7.2 MPa and 41.1 MPa, respectively, with high mechanical properties. After 28 days, the crystal transformation products and microstructures were shown. Figure 4 , mostly calcite crystals.
[0086] Example 2
[0087] A carbonate negative carbon cement, comprising the following solid raw materials in parts by weight: 75 parts of high-activity vaterite-type calcium magnesium carbonate ( Figure 2 Highly active vaterite calcium magnesium carbonate products), 25 parts of high active aragonite calcium magnesium carbonate ( Figure 2 Highly active aragonite type calcium magnesium carbonate product), 10 parts of sulphoaluminate cement, 10 parts of slag, 5 parts of amino acid, and 5 parts of melamine water reducer.
[0088] The raw materials of carbonate negative carbon cement were mixed in a stirring pot, stirred evenly for 5 minutes, and then water was added to the stirring pot at a water-to-solid ratio of 0.2. After stirring evenly for 3 minutes, a carbonate negative carbon cement slurry was obtained. The 72h hydration heat release curve of the prepared cement slurry is similar to Figure 3 The hydration heat release in 72 hours is 34 J / g solid. The cement paste is poured into the standard compression and flexural test block mold and placed at 40 degrees Celsius for carbonization and curing for 28 days. The curing carbon dioxide concentration is 40%. The flexural and compressive strengths at 28 days are 5.2 MPa and 32.1 MPa respectively, which has high mechanical properties. After 28 days, the crystal transformation products and microstructures are shown. Figure 4 , mostly calcite crystals.
[0089] Example 3
[0090] A carbonate negative carbon cement comprises the following solid raw materials in parts by weight: 50 parts of high-activity vaterite-type calcium magnesium carbonate ( Figure 2 Highly active vaterite calcium magnesium carbonate products), 25 parts of high active aragonite calcium magnesium carbonate ( Figure 2 Highly active aragonite calcium magnesium carbonate products), 25 parts of high active calcite calcium magnesium carbonate ( Figure 2 Highly active calcite type calcium magnesium carbonate product), 20 parts of aluminate cement, 10 parts of steel slag, 5 parts of tannic acid, and 5 parts of melamine water reducer.
[0091] The raw materials of carbonate negative carbon cement were mixed in a stirring pot, stirred evenly for 5 minutes, and then water was added to the stirring pot at a water-to-solid ratio of 0.2. After stirring evenly for 3 minutes, a carbonate negative carbon cement slurry was obtained. The 72h hydration heat release curve of the prepared cement slurry is similar to Figure 3 The hydration heat release in 72 hours is 61 J / g solid. The cement paste is poured into the standard compression and flexural test block mold and placed at 40 degrees Celsius for carbonization and curing for 28 days. The curing carbon dioxide concentration is 40%. The flexural and compressive strengths at 28 days are 4.7 MPa and 28.9 MPa respectively, which has high mechanical properties. After 28 days, the cement product product and microstructure are shown. Figure 4 .
[0092] Example 4
[0093] A carbonate negative carbon cement, comprising the following solid raw materials in parts by weight: 50 parts of hydrated calcium magnesium carbonate ( Figure 2 hydrated calcium magnesium carbonate products), 50 parts of high-activity vaterite calcium magnesium carbonate ( Figure 2 Highly active vaterite-type calcium magnesium carbonate product), 20 parts of magnesium oxide cement, 10 parts of concrete powder, 5 parts of chitosan, and 5 parts of polycarboxylate water reducer.
[0094] The raw materials of carbonate negative carbon cement were mixed in a stirring pot, stirred evenly for 5 minutes, and then water was added to the stirring pot at a water-to-solid ratio of 0.2. After stirring evenly for 3 minutes, a carbonate negative carbon cement slurry was obtained. The heat of hydration of the prepared cement slurry for 72 hours was similar to Figure 3 The hydration heat release in 72 hours is 78 J / g solid. The cement paste is poured into the standard compression and flexural test block mold and placed at 20 degrees Celsius for carbonization and curing for 28 days. The curing carbon dioxide concentration is 40%. The flexural and compressive strengths at 28 days are 7.7 MPa and 47.9 MPa respectively, which has high mechanical properties. After 28 days, the cement product product and microstructure are shown. Figure 4 .
[0095] Comparative Example 1
[0096] The difference between this comparative example and Example 1 is that the highly active vaterite-type calcium magnesium carbonate is replaced with currently commonly used calcium carbonate, and the rest is the same as Example 1. The results show that the hydration heat release in 72h is 39J / g solid, the 28d flexural and compressive strengths are 1.2MPa and 8.1MPa, respectively, there is no crystal transformation involved in the hydration process of the sample, and the mechanical properties are greatly reduced.
[0097] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A carbonate negative carbon cement, characterized in that: The composition comprises the following components in parts by weight: The calcium magnesium carbonate comprises a metastable calcium magnesium carbonate phase and a hydrous calcium magnesium carbonate phase, and a weight ratio of the metastable calcium magnesium carbonate phase to the hydrous calcium magnesium carbonate phase is 1:(0-1).
2. The carbonate negative carbon cement according to claim 1, characterized in that: The metastable calcium magnesium carbonate phase is an anhydrous crystalline phase, including at least one of vaterite calcium magnesium carbonate, aragonite calcium magnesium carbonate and calcite calcium magnesium carbonate; and / or, The hydrated calcium magnesium carbonate phase includes at least one of amorphous calcium magnesium carbonate, hexahydrate calcium magnesium carbonate, monohydrate calcium magnesium carbonate and hemihydrate calcium magnesium carbonate.
3. The carbonate negative carbon cement according to claim 1, characterized in that: The mass percentage of magnesium in the metastable calcium magnesium carbonate phase is 0.1-18%, and the average particle size is 0.1 μm-3 mm.
4. The carbonate negative carbon cement according to claim 1, characterized in that: The mass percentage of crystal water in the hydrous calcium carbonate magnesium phase is 5-60%, the mass percentage of magnesium is 0.1-20%, and the average particle size is 0.1 μm-10 μm.
5. The carbonate negative carbon cement according to any one of claims 1 to 4, characterized in that: The calcium magnesium carbonate is obtained by mixing cement-based materials with an active enhancer and then subjecting the mixture to carbonization treatment.
6. The carbonate negative carbon cement according to claim 5, characterized in that: The cement-based material includes at least one of concrete sand powder, steel slag, cement powder, slag, carbide slag, phosphogypsum, red mud and magnesium slag; and / or, The activity enhancer includes at least one of soluble magnesium salt, magnesium hydroxide, magnesium oxide, ethylenediaminetetraacetic acid, chitosan, tannic acid and amino acid.
7. The carbonate negative carbon cement according to claim 5, characterized in that: The total amount of the activity enhancer added is 1-10% of the mixture to be carbonized; and / or The carbonization treatment includes: introducing gas with a carbon dioxide concentration of not less than 5% for carbonization, and according to the solid mass of the cement-based material, the gas introduction rate is 0.01L / min / g-2L / min / g, and the introduction time is 1min-6h.
8. The carbonate negative carbon cement according to any one of claims 1 to 4, characterized in that: The clinker comprises at least one of Portland cement, sulphoaluminate cement, sulfate cement and magnesium oxide cement; and / or, The mineral admixture includes at least one of fly ash, slag, steel slag and concrete powder; and / or, The coagulation regulator includes at least one of soluble magnesium salt, phosphate, gypsum, ethylenediaminetetraacetic acid, chitosan, tannic acid, and amino acid; and / or, The water reducer includes at least one of lignin sulfonate water reducer, polycyclic aromatic salt water reducer, water-soluble resin sulfonate water reducer, naphthalene water reducer, aliphatic water reducer, amino water reducer and polycarboxylic acid water reducer.
9. A method for preparing carbonate negative carbon cement, characterized in that: include: Provide the raw materials of each component in the carbonate negative carbon cement according to any one of claims 1 to 8: The calcium magnesium carbonate, the clinker, the mineral admixture, the setting regulator and the water reducer are mixed to obtain the carbonate negative carbon cement.
10. A carbonate negative carbon cement product, characterized in that: The carbonate negative carbon cement prepared by the carbonate negative carbon cement according to any one of claims 1 to 8 and / or the preparation method of claim 9 is mixed with water and subjected to molding and curing treatment to obtain the carbonate negative carbon cement.
Citation Information
Cited By
Lightweight carbon sequestration type cement product and preparation method thereof
CN121872714A